Diseño de un banco de pruebas para medición de torque, velocidad angular, fuerza y potencia de motores de combustión interna de hasta 400 HP para la Universidad Antonio Nariño - Delgadillo Bernal, Brayan Stiven; Zapata Rodríguez, Juan David (Universidad Antonio Nariño, 2024)
The design of an internal combustion engine test bench was carried out, which serves the purpose of measuring the performance of engines and defining variables such as torque and maximum angular velocity for a detailed study. In addition to this, a detailed study of the combustion emissions generated was conducted to expand knowledge about engines for the students of the Antonio Nariño University.